Clonally Diverse Methicillin and Multidrug Resistant Coagulase Negative Staphylococci Are Ubiquitous and Pose Transfer Ability Between Pets and Their Owners - Gómez-Sanz, Elena; Ceballos, Sara; Ruiz-Ripa, Laura; Zarazaga, Myriam; Torres, Carmen (Frontiers in Microbiology, 2019)
Sixty-eight owners and 66 pets from 43 unrelated pet-owning households were screened for methicillin-resistant coagulase negative staphylococci (MRCoNS), potential cases of MRCoNS interspecies transmission (IT), and persistence. MRCoNS isolates were identified by microbiological and molecular tests. MLST-based phylogenetic analysis was performed in Staphylococcus epidermidis isolates. Antimicrobial susceptibility was evaluated by phenotypic and molecular methods. SCCmec type and presence of biofilm-related ica locus was PCR-tested. Isolates suspected for MRCoNS IT cases were subjected to SmaI-PFGE analysis and individuals from positive households were followed-up for one year for carriage dynamics (every three months, T0-T4). Nineteen MRCoNS isolates from owners (27.9%) and 12 from pets (16.7%) were detected, coming from 20 households (46.5%). S. epidermidis was predominant (90% and 67% of human and animal strains, respectively), showing high phylogenetic diversity (16 STs among 24 strains). MRSE strains belonged to CC5 (75%), CC11 (12.5%), singleton S556 (8.3%) and S560 (4.17%). Significant host-associated differences were observed for resistance to aminoglycosides, co-trimoxazol, chloramphenicol (higher in animal isolates) and tetracycline (higher among human strains). Multidrug resistance (MDR) was common (68.4%), and associated with human strains. Great diversity of ccr and mec complexes was detected, most strains being non-typeable, followed by SCCmecIV and V. Over one third of isolates (most from owners), carried the ica locus, all MRSE CC5. Two sporadic IT cases (T0) were identified in owner and dog from two households (4.7%), with diverse interspecies-exchanged clones detected along the sampling year, especially in dogs. Comparative analysis of all MRCoNS with all nasal coagulase positive staphylococci (CoPS) recovered from the same individuals at T0 revealed that CoPS alone was predominant in owners and pets, followed by co-carriage of CoPS and MRCoNS in owners but single MRCoNS in pets. Statistical analyses revealed that owners are more prone to co-carriage and that co-existence of IT cases and co-carriage are positively interrelated. MRCoNS from healthy owners and their pets are genetically heterogeneous MDR strains that are spread in the community. Therefore, pets also contribute to the dissemination of successful human clones. Owner-pet inhabitancy increases the risk for staphylococcal temporal concomitance with its subsequent risk for bacterial infection and genetic exchange.